2016
DOI: 10.1016/j.jtcvs.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent outcomes after coronary artery bypass graft surgery performed by consultant versus trainee surgeons: A systematic review and meta-analysis

Abstract: With appropriate supervision, conventional CABG can be performed by trainee surgeons without an adverse impact on perioperative outcomes or midterm survival. Data regarding off-pump CABG are limited, and further research is warranted to ascertain the impact of trainee operator status on long-term outcomes after off-pump CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
3
13
0
Order By: Relevance
“…Interestingly, the presence of trainees was not associated with worse mortality and all the outcomes considered in our study were similar when comparing cases done with trainees' involvement or not. These findings confirmed previously published data from the United Kingdom regarding esophageal surgery in particular and many other studies that have looked at trainee's involvement with cardiac and noncardiac surgery [21][22][23]. It is comforting that we can continue to teach complex surgeries to young trainees without compromising results.…”
Section: Commentsupporting
confidence: 87%
“…Interestingly, the presence of trainees was not associated with worse mortality and all the outcomes considered in our study were similar when comparing cases done with trainees' involvement or not. These findings confirmed previously published data from the United Kingdom regarding esophageal surgery in particular and many other studies that have looked at trainee's involvement with cardiac and noncardiac surgery [21][22][23]. It is comforting that we can continue to teach complex surgeries to young trainees without compromising results.…”
Section: Commentsupporting
confidence: 87%
“…Multiple studies examining non‐vascular surgery have demonstrated the safety of having trainee surgeons perform operations under supervision 7–9 . Our findings are similar to those previously published regarding the surgical training of carotid endarterectomies in Europe.…”
Section: Discussionsupporting
confidence: 89%
“…Performing MAG is undoubtedly technically demanding and patient's safety should always be a concern when training young surgeons. The effect of training on clinical outcome after cardiac surgery has been the subject of previous publications [14][15][16][17]. However, to the best of our knowledge, this is the first study which compared outcomes in patients undergoing CABG with MAG performed by residents versus attending surgeons and we found that the two groups had comparable short term outcomes and long term survival.…”
Section: Discussionmentioning
confidence: 64%